Criminal Mediation in the Settlement of Unlicensed Small-Scale Mining Crimes in the Jurisdiction of the East Java Regional Police - Qoirul Khitam Bastomi; I Nyoman Nurjaya; Istislam Istislam (Jurnal Ius Constituendum, 2025)
This study aims to analyze the effectiveness of the penal mediation approach in resolving illegal mining crimes (PETI) in the jurisdiction of the East Java Regional Police, which has been dominated by a repressive approach and has caused complex social, economic, and ecological problems. The repressive approach has failed to address the root causes of the problem, and PETI is often carried out by economically vulnerable groups due to an inclusive bureaucracy. The research method employed is a sociological-legal approach, combining normative analysis of legal regulations (das sollen) with empirical studies of law enforcement practices in the field (das sein). The research findings indicate that criminal mediation has gained legal legitimacy through various regulations, including the 2023 National Criminal Code, Police Regulation No. 8 of 2021, and Regulation No. 15 of 2020. In East Java, 393 PETI cases were resolved using this approach during 2023–2024, preventing 1,650 offenders from conventional litigation and saving law enforcement budgets. This approach reflects the renewal of Indonesian criminal law, which not only punishes but also restores and empowers. This study provides empirical evidence on the application of panel mediation in environmental criminal cases, an area rarely explored in previous research.